Tracking demands for seeking psychological help before and during the COVID-19 pandemic: a quanti-qualitative study - Bruna M. C. Coutinho; Luis F. C. Anunciação; Jesus Landeira-Fernandez; Thomas E. Krahe (Psicologia: Reflexão e Crítica, 2023)
Abstract The COVID-19 pandemic has placed unprecedented burdens on individuals and communities around the world. The isolation, fear, and uncertainty caused by the virus has led to increased rates of anxiety, depression, and other mental health issues. The pandemic has also had a disproportionate impact on individuals and communities with low income and socioeconomic status. Objective To shed light on the consequences of the pandemic on individuals from minorities and low-income areas, we investigate the main reasons that led patients who were referred to a social clinic of a private university in Rio de Janeiro to seek psychological treatment before (2019) and during the pandemic (2020 and 2021). Methods We conducted a quanti-qualitative study with a lexical analysis that evaluated 549 complaint forms of patients seeking treatment in these two distinct periods. Our analyses included descending hierarchical analysis (DHA) and correspondence factor analysis (CFA). Results Family dynamics and communication factors play a dominant role in the reason for seeking therapy and psychological treatment. Additionally, our study suggested an increase in anxiety and panic attacks among other mental health issues associated with grief and losses during the pandemic years. Conclusion Based on these analyses, we can begin to identify a few changes in the main demand and redirection of complaints of patients during the period of COVID-19.